Approaches to Records Management for Community Services by Voluntary Social Clubs in Northern States, Nigeria - Bube, Abdulkarim Aliyu; Mohammed , Zakari; Abubakar , Tijjani; Mohammed , Habibu (Communicate: Journal of Library and Information Science, 2024)
This study focuses on approaches to records management for community services by voluntary social clubs in Northern States, Nigeria. Descriptive cross-sectional survey research design was adopted for this study. The population of this study comprise the members of Voluntary Social Clubs in Northern States of Nigeria totaling eighty four (84). The researcher used the entire members of the population of this study. The instrument for data collection was questionnaire. Descriptive statistics was used in analysing the data used to answer the research questions. Inferential statistics of Kruskal Wallis was used in analysing all the hypotheses formulated in this study. It was found out that majority of the respondents agreed that the types of records generated in the process of community service in Northern States, Nigeria, were posters. The procedures through which records were managed were through the use of computers as well as shelves and the procedures through which records were accessed were through the use of title of the records as well as folders of the records among others. It is concluded that records management was carried out through approaches for community services by Voluntary Social Clubs in Northern States, Nigeria. It is recommended that members of the Voluntary Social Clubs should consider procedures such as regulating the excessive temperature of the records storage place as well as the use of box as procedures through which records are managed. ,,,,,